2015
DOI: 10.1016/j.lwt.2014.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Production of dulce de leche: The effect of starch addition

Abstract: a b s t r a c tThis study evaluated the effect of addition of modified starch on the characteristics of dulce de leche, being conducted in two phases. In the initial phase, starches were evaluated for their ability to provide viscosity in model solutions representing the composition of dulce de leche during processing, thus evaluating the effect of solid concentration, which occurs during production, on the ability of starches to increase viscosity in simulated conditions of heat treatment and agitation promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
4
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 4 publications
4
34
4
9
Order By: Relevance
“…Similar results were observed by Silva et al (2015). Machado and Viotto (2007) demonstrated that the addition of 0.75% of modified starch and 45% of whey provided the obtainment of sweet with no lactose crystals until the ninth month of storage.…”
Section: Storage Time Effectsupporting
confidence: 81%
See 3 more Smart Citations
“…Similar results were observed by Silva et al (2015). Machado and Viotto (2007) demonstrated that the addition of 0.75% of modified starch and 45% of whey provided the obtainment of sweet with no lactose crystals until the ninth month of storage.…”
Section: Storage Time Effectsupporting
confidence: 81%
“…5 -473.7, 20.54 -36.28, 18.08 -19.45, 0.83 -0.94, 255.9 -431.1, respectively, commercial samples of 'Dulce de Leche' by Silva et al (2015).…”
Section: Storage Time Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Silva et al (2014), the use of starch in 'dulce de leche' may contribute to its consistency and efficiency by the retention of water, helping to control the crystallisation of lactose, which confers a sandy soil texture to the final product.…”
Section: Introductionmentioning
confidence: 99%